Study on Thermal Deformation of Tilting Tile Thrust Bearing under Oil Injection Lubrication Condition - LI Yong-hai; SHEN Jian; SUN Xiang-zhi; MA Shen; WU Ding-chao (Journal of Harbin University of Science and Technology)
The oil film temperature field of thrust tile surface of tilting pad thrust bearing was obtained according to heat transfer，tribology and other related theories. By using the finite element numerical analysis method，the paper mainly introduces the application method of the temperature load on the upper surface of the thrust pad and the calculation and loading method of the heat transfer coefficient on the rest surface of the thrust pad，and the numerical simulation solution of the deformation caused by the temperature of the thrust pad of the tilting pad thrust bearing. Ｒesults: the maximum deformation of thermal deformation of thrust shoe is close to the oil discharging edge，and the overall deformation expands outward along the four sides of the warping and is convex in the middle，and its deformation has reached the same order of magnitude as the oil film thickness.